Maximizing tendency predicts university adjustment and academic performance - Li, Mushi; Jia, Huiyuan; Wang, Haixia (Frontiers in Psychology, 2023)
Decision-making characteristics that contribute to university adjustment and academic performance have been important topics in the research on success in higher education. This study proposes a new perspective that maximizing tendency, as a decision-making style, influences adaptive outcomes in college life. Two studies were performed to investigate the positive effects of maximizing tendency on university adjustment and academic performance. In the final data, 552 students in Study 1 and 309 students in Study 2 were analyzed. The results revealed that maximizers among students have better university adjustment after their first year at school and achieve higher GPAs when they finished their bachelor’s degree. Furthermore, eudaimonic well-being mediated the relationship between maximizing tendency and university adjustment (Study 1), whereas university adjustment mediated the relationship between maximizing tendency and college student’s academic performance (Study 2). These consistent results imply that maximizing decision-making style is a predictor of university adjustment and academic performance.